Production of virgin coconut oil via centrifugation and oven methods - Mohamad Fariz, Ahmad (2009)
The conventional ways of breaking emulsions using heat is disadvantageous from the both economic and environmental perspectives. In this study, the production of virgin coconut oil from coconut oil milk was investigated. Centrifugation and hot method were used for separation of oil. Analysis was carried out by gas chromatography. Results show that, production of virgin coconut oil increases with increasing centrifugal speed. The optimum temperature required to maintain the nutrition oil oil was found to be 60oC. Experimental data also presented to show the influence of Triton –X-100, Tween 20 and SDDS on stability of virgin coconut oil emulsion.